2009
DOI: 10.1897/08-592.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Trace Metals in Soil as Affected by Soil Type and Aging After Contamination: Using Calibrated Bioavailability Models to Set Ecological Soil Standards

Abstract: Total concentrations of metals in soil are poor predictors of toxicity. In the last decade, considerable effort has been made to demonstrate how metal toxicity is affected by the abiotic properties of soil. Here this information is collated and shows how these data have been used in the European Union for defining predicted-no-effect concentrations (PNECs) of Cd, Cu, Co, Ni, Pb, and Zn in soil. Bioavailability models have been calibrated using data from more than 500 new chronic toxicity tests in soils amended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
292
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(315 citation statements)
references
References 41 publications
(66 reference statements)
16
292
2
5
Order By: Relevance
“…This was also observed in the sorption experiments (Table 3), in which the Säby soil sorbed a higher percentage of the added vanadium than the Pustnäs soil. The results of the plant growth assays confirmed earlier observations that toxicity assays performed on soils freshly spiked with metal salts have a relatively large fraction of bioavailable metal [35]. The EC50 values for barley plants grown in freshly spiked Pustnäs and Säby soils were 87 and 230 mg V kg -1 soil respectively [15].…”
Section: Soils Amended With Blast Furnace Slagsupporting
confidence: 85%
See 1 more Smart Citation
“…This was also observed in the sorption experiments (Table 3), in which the Säby soil sorbed a higher percentage of the added vanadium than the Pustnäs soil. The results of the plant growth assays confirmed earlier observations that toxicity assays performed on soils freshly spiked with metal salts have a relatively large fraction of bioavailable metal [35]. The EC50 values for barley plants grown in freshly spiked Pustnäs and Säby soils were 87 and 230 mg V kg -1 soil respectively [15].…”
Section: Soils Amended With Blast Furnace Slagsupporting
confidence: 85%
“…In our case, the reference material is the freshly spiked soil. A similar approach was used by Smolders et al [35] when they evaluated the leaching-ageing factor quantifying the differences in ED10 values between freshly spiked and aged soils. An RBA factor below unity indicates reduced bioavailability in relation to the freshly spiked soils.…”
Section: Resultsmentioning
confidence: 99%
“…Data on Pb uptake in earthworms show striking differences with Pb body burdens of 75.6 AE 46 mg/kg in Lumbricus castaneus collected from soil containing 412 to 79,963 mg Pb/kg (Terhivuo et al, 1994), and 348 AE 72 mg Pb/kg in L. castaneus exposed to soil containing only 200 mg Pb/kg (Svendsen et al, 1996). Kabata-Pendias and Pendias (1992) concluded that Pb concentration in the soil solution is a better indicator of adverse effects on biota than total soil Pb levels, with metal ions determining toxicity (Smolders et al, 2009). In contrast, Davies (1992), Grelle and Descamps (1998) and Booth et al (2003) found that Pb uptake in plants and earthworms was predicted best using total soil Pb concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A significant (p ≤ 0.05) decrease in Pb toxicity was found with leaching for nine soils (53% of soils) for EC10 values, nine soils (53%) for EC20 values, and 12 soils (71%) for EC50 values. The leaching factor (LF) listed by Smolders et al (2009) was determined by calculating the ratio of ECx in leached soil to the corresponding ECx in unleached soil, which was used to correct ecotoxicity data. Overall, for soils where SIN was inhibited sufficiently to determine the EC10 and EC20 values, LF values ranged from 0.4 to 17.84 and from 0.68 to 12.46, respectively.…”
Section: Dose-response Curves and Toxicity Thresholds In Leached Andmentioning
confidence: 99%
“…Aging processes and loss of excess salts by leaching may contribute much to this discrepancy (Oorts et al, 2006a). Therefore, leaching after metal addition has been proposed as an agreed approach to reduce the chemical artifacts of the spiking procedure (e.g., salt effect, increased metal solubility) that can decrease the ecological relevance of soil toxicity assays (Schwertfeger, 2011;Smolders et al, 2009;Oorts et al, 2006aOorts et al, , 2007Bongers et al, 2004;Stevens et al, 2003). The effects of leaching on Pb ECx values in soils require further study on a larger scale before leaching is used as a standard protocol in soil toxicity assays.…”
Section: Introductionmentioning
confidence: 99%